A Reflective Study on SEA Teacher Practice: from Thailand to Indonesia - Ima Widyastuti; Kewwalee Kumyai (Universitas Sarjanawiyata Tamansiswa, 2019)
The goal of the Pre-service teacher program or SEA Teacher Program under the SEAMEO are for providing the experience to the partner universities in teaching internationally, improving their English skills, as well as expanding their worldwide networking and knowledge. Through the program the students require to do observation, teaching assistance, teaching, and reflection on what they experience at the pointed schools. Though the program is well established, however, some lacks are still existed. The present study aims to reflect what the four participants experience during the pre-service teacher program. The discussion of the interview and observation data is conducted under the reflective study on four points namely school and class observation, teaching assistance, teaching, and reflection.